Knitting Togetherness among the Allied Malay: Aceh â Minangkabau â the Malay Peninsula - Madjid, M Dien (ASPENSI in Bandung, Indonesia, 2012)
ABSTRACT:Â In the 15th â 16th centuries AD (Anno Domini), the trade map of the Malay peninsula is so inclusive; the Malacca strait was preoccupation with the activities of foreign trade fleet from Europe, the Middle East, India, and some other centers of world civilization. Referring to the constellation of Malay world trade, which was increasingly exotic, the Malay civilization and culture became higher. The Malay language became the lingua franca used in the commerce world of Malay at the time. This paper tries to elaborate the growth of Malay civilization that could not be separated from the shaft of Aceh â Minangkabau â Malay Peninsula. Aceh played the role of elites who held political supremacy of the Malay world, while Minang and the Malay Peninsula â in this case held by the related palace elites â held a position as the locus of proliferator in the aspects of sociological, anthropological, and the Malay culture became a major cultural identity in Southeast Asia for centuries to the present.Â KEY WORDS: Allied Malay, Aceh, Minangkabau, Malay peninsula, interaction of the Malay, national awareness, and Malay ideology.About the Author: Prof. Dr. M. Dien Madjid is a Professor of History at the Faculty of Adab and Humanities UIN (State Islamic University) Syarif Hidayatullah in Jakarta, Indonesia. He can be reached at: dr.dienmadjid@yahoo.comÂ How to cite this article? Madjid, M. Dien. (2012). âKnitting Togetherness among the Allied Malay: Aceh â Minangkabau â the Malay Peninsulaâ in TAWARIKH: International Journal for Historical Studies, Vol.4(1) October, pp.1-20. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (August 25, 2012); Revised (September 28, 2012); and Published (October 28, 2012).